The economic impact of free trade agreements with Asia on the US pork industry - Ahlen, Lindsey (Kansas State University, 2016)
For the past 25 years, Free Trade Agreements (FTA) in Asia have been increasing. This allows for a potential expansion of exports into Asia for a variety of goods. However usually these agreements have not covered agricultural products. The most recent multilateral agreement currently includes agricultural products and agricultural trade. U.S. pork exports have been on the rise with Asian countries. Trade openness with Asian countries allows U.S. pork companies to gain a market in the region. This thesis estimates the economic impact that FTA’s and multilateral agreements have on pork exports, through the level of open markets measured by Freedom House. Using regression analysis, this research examines the determinants to U.S. pork exports, where trade openness is a major independent variable. Pork is a popular meat preference in East Asia. A regression analysis was estimated to determine the shift along the demand curve of U.S. pork exports to three East Asian countries, China, Japan, and South Korea. Overall all three countries showed their trade openness being weakly associated with the U.S. pork export demand to that particular country during the years of 1995–2013.
Keywords: Pork; Trade; East Asia; Agriculture, General (0473)